Estudio jurídico de la especificación como modo de adquirir el dominio de los bienes.- propuesta de reforma al código civil - Portocarrero Ramos, Harol Stiven (2015)
Our legislation within its title II title in what has to do with the domain , its art. 603 modes of acquiring ownership , which are: occupation , accession , the tradition , the succession because of death, adverse possession ; This classification is important because when the mode is native to measure the scope of the right that is acquired simply meet the owner and nothing else ; sufficient to examine the event or action that sets the mode and the thing upon which rests . So if, for example , is acquired by occupation, will have to cater exclusively to the act of occupation. In the case of acquisitions of derivatives, to see the extent , strength , perfection the way, we must also attend to the right had the other owner, the ancestor , because no one can transfer or convey more rights than they have . Therefore, in the tradition , if the transferor does not own , does not transfer the domain ; and the thing is mortgaged, it is with the mortgage; and the cause does not transmit to heirs but the rights you have. •  There are two modes that are generally singular title : tradition and prescription, except in the case of the sale or prescription of an estate , where they operate a universal title. According requiring pecuniary sacrifice, the means of acquiring are gratuitously onerous. The mode of acquisition is free of charge, when you purchased your domain makes no pecuniary sacrifice : the occupation , accession , the prescription ;succession upon death; and eventually the tradition. It is for consideration when the purchaser must make a consideration pecuniary : tradition be a consideration when the title has the same property (sale, for example), while it will be a way free of charge, if the title is (donation , for example). The issue we address and study more we go on talking about the accession , which is acquired by the way of which the owner of a thing is changed to what it produces , or what she joins . Products are things natural and civil fruits. The same Civil Code explains that natural fruits are those given by nature helped or not of human industry and civil fruits constitute those prices , pensions or lease rentals and interest on capital payable or tax background lost. Further notes that civilians are called fruit are pending while ; and perceived , from being charged. Based on the annotated definitions, I can express my personal opinion in the sense that the accession , is a way to acquire originating supported by the natural, legal , logical and essential that the owner of a thing , it is also a criterion the fruit it produces as well as it is also of the things that accede to lose their individual nature. The main domain allows the generation of the accessory. We must also mention that there is debate among scholars as to the legal nature of the accession , because while some claim that this is an original way to acquire ownership of the fruits , creating a new legal status in the resulting thing , others say that the property lies with the fruits or things that stick . In accession the Civil Code defines as another kind of accession is the specification , which is verified when , matter belonging to a person , another person makes a work or any appliance ; like grape wine is made outside, silver or a drink outside. Throughout the development , conceptual, doctrinal and legal we realize that does not contain the essential requirements to be considered as accession , since there is not the quality of the principal and accessory, in this case the work of the person to perform new device can not be regarded as a thing appropriated by man and by virtue work can not be regarded as principal or accessory , so the issue has been addressed " LEGAL STUDY OF tHE SPECIFICATION AS HOW TO ACQUIRE tHE DOMAIN OF PROPERTY . - PROPOSED AMENDMENT TO CIVIL CODE”